(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2020)
Regulatory and institutional innovation in Agri-Food Law is a central topic of the research of those years, both in the domestic and in the European dimension. In this context, the relationship between technological innovation and legal innovation is a central and qualifying dimension. An analysis, albeit short, of the experiences of these years allows us to identify the emergence, with increasing evidence, of a multilevel legal corpus, which builds up rules intended for the agri-food system, addressed to include the whole set of structures, activities and relationships, subject to multi-level regulatory interventions, and thus proposes a sort of open laboratory, which moves towards a complex polycentric system of regulation, in which global, European and domestic levels intertwine, and public and private responsibilities operate, carried out to a systemic framework through vertical and horizontal cooperation and subsidiarity.